The Economist technology quarterly September 22nd 2001. (Economist, 2001)
A special section on technological innovations. Topics discussed include the technology boom and the economic cycle; wireless networking; how transparent concrete is encouraging architects to rethink their building designs; efforts to create an artificial retina; a new liquid-crystal display; magnetic memory chips; using transdermal technology to administer drugs through the skin; digital archival repositories; the “mu-chip” wireless identification device; agile programming; programming languages for writing software; the development of satellite technology; artificial intelligence; electronic directories; drug companies reaping the rewards of genomics; and chip innovator Carver Mead.